2020
DOI: 10.1088/1755-1315/418/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ascorbic acid on clove (Syzigium aromaticum) grafting

Abstract: Clove plants can be generatively propagated by seeds and vegetatively by grafting. However, the success of clove grafting is still low (<50%), presumably due to the high content of phenol in the stem which inhibits callus formation and causes connection failure. The aim of the study was to obtain the best ascorbic acid concentration to reduce phenol content in the clove stem. The study was conducted at the Ecophysiology Laboratory, ISMCRI from January to June 2019. The study was arranged in randomized block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The epicotyl grafting is a grafting technique when the rootstock still has an epicotyl. Grafting technology is also applied to jackfruit [21], walnut [22], cashew [23], mango plants [24], and clove [25]. The stages of nutmeg grafting to produce a successful grafting > 80 are as follows (Figure 2): In the epicotyl grafting technology on nutmeg, what needs to be tried is the bonding of the rootstock with the scion.…”
Section: Epicotyl Grafting Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The epicotyl grafting is a grafting technique when the rootstock still has an epicotyl. Grafting technology is also applied to jackfruit [21], walnut [22], cashew [23], mango plants [24], and clove [25]. The stages of nutmeg grafting to produce a successful grafting > 80 are as follows (Figure 2): In the epicotyl grafting technology on nutmeg, what needs to be tried is the bonding of the rootstock with the scion.…”
Section: Epicotyl Grafting Techniquementioning
confidence: 99%
“…Until now, they are still using plastic straps. The material that has the potential to be used is silicone hose and has been applied to clove grafting [25]. Grafting results are of better quality and require less time.…”
Section: Epicotyl Grafting Techniquementioning
confidence: 99%
“…These techniques facilitate the early detection of graft incompatibility and provide a model for a more accurate analysis of the grafting phenomenon (Suryadi et al, 2020). Jonard et al (1990) reported the possibility of predicting graft incompatibility of apricot and lemon trees using in vitro techniques (e.g., internode association and callus fusion).…”
Section: Introductionmentioning
confidence: 99%